Frequency of Prediabetes in Acute Stroke Patients Presenting at Tertiary Care Hospital, Karachi - Guriya; Jabeen, Rukshanda; Soniya; Ejaz, Ayesha; Gul, Lubna; Kumar, Aakash (Indus Journal of Bioscience Research, 2025)
Background: Prediabetes, an intermediate state of abnormal glucose metabolism, is increasingly recognized as a risk factor for cardiovascular disease, including stroke. However, limited local data exist on its prevalence among acute stroke patients in Pakistan. Objective: To determine the frequency of prediabetes in patients presenting with acute stroke at a tertiary care hospital in Karachi. Methods: This cross-sectional study was conducted at a tertiary care hospital in Karachi. A total of 189 patients admitted with a diagnosis of acute stroke were included. Demographic data, clinical history, and laboratory findings were recorded. Prediabetes was defined random blood sugar 100 to 125 mg/dL. Data were analyzed using descriptive statistics and chi-square tests to identify associations between prediabetes and baseline variables. Results: Out of 189 patients, 53 (28%) were identified with prediabetes. Prediabetes was more frequent in the 40–60 years age group (43.1%) compared to older patients (20.2%) (p = 0.01). No significant association was found between prediabetes and gender (p = 0.29) or hypertension (p = 0.17). However, a statistically significant association was observed between prediabetes and dyslipidemia (p = 0.01). Smoking status also showed a marginal association with prediabetes (p = 0.05). Conclusion: A considerable proportion of acute stroke patients had prediabetes, particularly among middle-aged individuals. Routine screening for prediabetes in stroke patients may help identify at-risk individuals early and enable timely interventions to prevent diabetes and recurrent vascular events.